Nrf2 signalling pathway and autophagy impact on the preventive effect of green tea extract against alcohol-induced liver injury. (20th April 2021) - Zhang, Yu-Pei; Yang, Xue-Qin; Yu, Dong-Ke; Xiao, Heng-Yi; Du, Jun-Rong
Abstract: Objectives: To explore the potential molecular mechanism underlying the effect of green tea extract (TE), rich in tea polyphenols (TPs), on improving alcohol-induced liver injury. Methods: Mice were intragastrically treated with 50% (v/v) alcohol administration (15 ml/kg BW) with or without three doses of TE (50, 120 and 300 mg TPs/kg BW) daily for 4 weeks, and biological changes were tested. Key findings: The TE improved the functional and histological situations in the liver of the mice accepted alcohol administration, including enzymes for alcohol metabolism, oxidative stress and lipid accumulation. Interestingly, the TE increased the nuclear translocation of nuclear factor erythroid-2-related factor 2 (Nrf2), with the decreasing expression of kelch-like ECH-associated protein 1 (Keap1), indicating the association between the effect of TE with Nrf2-mediated antioxidant signalling. Moreover, the TE restored the activity of autophagy, showing as lifted Beclin-1 expression, LC3B-II/LC3B-I ratio, and decreased p62 expression. Importantly, all these effects were dose-dependent. Conclusions: These findings provide a new notion for the first time that the TE preventing against alcohol-induced liver injury is closely related to accelerated metabolism of alcohol and relieved oxidative stress, which is associated with Nrf2 signalling activation and autophagy restoration, thus the reduction of lipid accumulation in liver. Graphical Abstract: